The Scales of Psychological Well-Being – a validation, usability and test–retest study among community-dwelling older people in Finland. (4th May 2021) - Saajanaho, Milla; Kokko, Katja; Pynnönen, Katja; Tourunen, Anu; Törmäkangas, Timo; Portegijs, Erja; Rantanen, Taina
Abstract: Objectives: To validate the Finnish version of the 42-item Scales of Psychological Well-Being among community-dwelling older people. The study also examined the test–retest reliability and usability, i.e. user experience, of the scales in this age group. Method: The 42-item version of the SPWB was administered as part of a face-to-face interview among 968 men and women aged 75, 80 or 85 years. The subsample for test–retest analyses comprised 42 participants, who in addition to 11 interviewers also answered questions concerning the usability of the scales. Exploratory and confirmatory factor analyses, Cronbach's alpha coefficients, Pearson and intra-class correlation coefficients, and Kendal's Tau B were used in the analyses. Results: The factor analyses did not support the theory-based six-factor structure of the scales. The Cronbach's alphas showed high internal consistency reliability for the total scale, but modest for the subscales. The intercorrelations between the subscales were moderate. The total score and the subscale scores of the SPWB correlated positively with quality of life and life satisfaction, and negatively with depressive symptoms. The interviewers reported that while most of the participants responded to the scales without marked difficulties, others could only answer after clarifications of some statements. Discussion: The reliability of the 42-item version of the SPWB was modest. The factor structure was inconsistent among the three age groups studied, but the scales were feasible to use. The current results call for further methodological consideration to optimize assessment of eudaimonic well-being in old age.